The role of pre-existing knowledge and knowledge acquisition in internet-based cognitive-behavioural therapy for eating disorders. (September 2022) - Linardon, Jake; Broadbent, Jaclyn; Shatte, Adrian; Fuller-Tyszkiewicz, Matthew
Abstract: Knowledge is a relevant concept in internet-based cognitive-behaviour therapy (I-CBT), yet little research has sought to understand the role of knowledge in I-CBT for eating disorders. This study addressed this gap. Data were analysed from 293 participants enrolled in a RCT of I-CBT for eating disorder symptoms. A test assessing knowledge of CBT principles and eating disorders was administered before and after I-CBT. Participants had high knowledge to begin with, correctly answering 72% of items. A significant increase in knowledge scores and knowledge confidence was observed after ICBT. While no relationship between the degree of knowledge gain and the degree of symptom improvement emerged, an increase in confidence in one's knowledge was associated with greater symptom improvement. Higher baseline knowledge levels predicted lower likelihood of drop-out and a higher likelihood of adherence, but were unrelated to symptom-level improvement. Findings suggest that while new knowledge can be acquired through I-CBT, the degree of knowledge gain alone is not sufficient to explain improvement in symptoms. Pre-existing knowledge levels may be an important prognostic indicator of patient progress and compliance to I-CBT. Ensuring that patients can correctly apply the key I-CBT skills may be more important than knowledge gain. Highlights: Participants improve their knowledge of CBT after internet-based interventions. An increase in knowledge confidence predicts greater symptom improvement. Higher baseline knowledge levels predicted lower dropout and greater compliance to I-CBT. Knowledge may be an important prognostic indicator in I-CBT.